2021
DOI: 10.1111/mec.16114
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent dispersal determines relatedness and genetic structure in a patchy amphibian population

Abstract: Dispersal is a central process in ecology and evolution with far reaching consequences for the dynamics and genetics of spatially structured populations (SSPs). Individuals can adjust their decisions to disperse according to local fitness prospects, resulting in context-dependent dispersal. By determining dispersal rate, distance and direction, these individual-level decisions further modulate the demography, relatedness and genetic structure of SSPs. Here, we examined how context-dependent dispersal influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 106 publications
(212 reference statements)
1
6
2
Order By: Relevance
“…Landscape movements requiring individuals to move from mature forest to or through regenerating forests were rare; these movements had the lowest mean and variance of all landscape movements. Similar informed dispersal has been seen in other spatially-structured populations where individuals favor higher quality habitats [4,53,54]. Moreover, Rittenhouse and Semlitsch (2006) found that adult Ambystoma maculatum avoid crossing grassland habitat and our findings suggest that regenerating clearcuts may have similar negative effects on the probability of colonization if situated between a source and destination pond for dispersing animals [55].…”
Section: Factors Influencing Local and Landscape Movementssupporting
confidence: 85%
“…Landscape movements requiring individuals to move from mature forest to or through regenerating forests were rare; these movements had the lowest mean and variance of all landscape movements. Similar informed dispersal has been seen in other spatially-structured populations where individuals favor higher quality habitats [4,53,54]. Moreover, Rittenhouse and Semlitsch (2006) found that adult Ambystoma maculatum avoid crossing grassland habitat and our findings suggest that regenerating clearcuts may have similar negative effects on the probability of colonization if situated between a source and destination pond for dispersing animals [55].…”
Section: Factors Influencing Local and Landscape Movementssupporting
confidence: 85%
“…Overall, our models of group dynamics suggest that small groups can theoretically be rescued from extinction by group augmentation via immigration, and our empirical results suggest that smaller groups present more breeding opportunities that should attract more immigrants than larger groups. However, this may rarely happen due to the individual fitness benefits pursued by immigrants and their apparent preference to join larger groups, condemning smaller groups to a higher risk of extinction ( 65 , 66 ) as has been shown in other cooperatively breeding societies governed by group augmentation benefits ( 33 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nearest native northern crested newt population is located over 40 kilometres away as the crow flies (well beyond the lifetime dispersal distance; Arntzen and Wallis, 1991;Kupfer and Kneitz, 2000;Haubrock and Altrichter, 2017;Unglaub et al, 2021). It is unclear if the isolated population in the coastal dunes is the remnant of a formerly larger natural distribution (Creemers and van Delft, 2009).…”
Section: Introductionmentioning
confidence: 99%